Penyuluhan Hukum tentang Hak dan Kewajiban Warga Binaan Berdasarkan UU Nomor 22 Tahun 2022 tentang Pemasyarakatan - Alfonsus Hendri Soa; Sy Hasyim Azizurrahman; Plasma Versiana Mukti; Sri Ismawati; Hermansyah Hermansyah; Aswandi Aswandi; Parulian Siagian; Herlina Herlina; Mega Fitri Hertini (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Community Service (PKM) which is the main focus is about the awareness of inmates on their obligations as stated in Law Number 22 of 2022 concerning Corrections at the Class IIA Pontianak Women's Prison. This activity has a goal to enhance the understanding among inmates about their duties regarding compliance with laws, maintaining security and cleanliness, participating in development programs, and respecting other people's rights during the correction process. Based on observations, interviews, and legal counseling, it was discovered that some inmates do not yet fully understand their obligations. Counseling has provided a better understanding of the reciprocal relationship between obligations and rights, including remission and parole. The results also indicate that there is room for improvement through continuous mentoring and more transparent oversight mechanisms so that the correctional system can function effectively, fairly, and with an orientation toward social reintegration.to realize a humanistic, equitable, and gender-sensitive development system.